AGAMA DAN NILAI SPRITUALITAS - Nurliana Damanik (UIN Sumatera Utara Medan, 2022)
Human needs for religion cannot be denied other than because humans have religious nature, humans need religion because humans who have perfection and lack and also humans are always presented with challenges to be able to go through various problems so humans need to be fortified with religious values. And with the true values of spirituality life peace can be realized. Spirituality is essentially a concern across religions and races. And what is clear is that spirituality is a concern for cross beings. Spirituality which is an innate human instinct is an important point in the birth of religion. Religion can last for a long time. And also as a place to be able to preserve spiritual experiences.